2011
DOI: 10.4148/2378-5977.7141
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding copper and feed-grade antimicrobials on the growth performance of weanling pigs (2011)

Abstract: A total of 240 weanling pigs (34 d of age with an average body weight of 17.1 lb) were used in a 35-d growth trial to compare the growth performance effects of copper (Cu) and feed-grade antimicrobials. The 6 dietary treatments were arranged in a 2 Ã-3 facto-rial with 2 added Cu levels (basal level of 16.5 ppm or basal + 125 ppm from copper sulfate) and 3 antimicrobial treatments including a control, chlortetracycline (CTC; Alpharma, Fort Lee, NJ) at 500 g/ton (10 mg/kg BW), and tylosin (Tylan; Elanco Animal H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Other three studies in weaned piglets showed that dietary tylosin supplementation at 100–110 mg/kg feed did not affect performance of piglets (Amachawadi et al. ( 2011 ), 100 mg tylosin/kg feed; Harvey et al. ( 1995 ) and Weber and Kerr ( 2008 ), 110 mg tylosin/kg feed).…”
Section: Assessmentmentioning
confidence: 97%
See 1 more Smart Citation
“…Other three studies in weaned piglets showed that dietary tylosin supplementation at 100–110 mg/kg feed did not affect performance of piglets (Amachawadi et al. ( 2011 ), 100 mg tylosin/kg feed; Harvey et al. ( 1995 ) and Weber and Kerr ( 2008 ), 110 mg tylosin/kg feed).…”
Section: Assessmentmentioning
confidence: 97%
“…Amachawadi et al. ( 2011 ) studied the effect of feed grade antimicrobials and copper on performance in pigs. A total of 240 weaned piglets (unspecified breed/genotype; 34 days of age with an average BW 7.7 kg) were used in a 35‐day growth trial to compare the effects of copper (Cu, from copper sulfate) and feed grade antimicrobials in a 2 × 3 factorial design (the factors being copper level 16.5 and 141.5 mg Cu/kg feed and antimicrobial level 0‐control or chlortetracycline or tylosin supplementation).…”
Section: Assessmentmentioning
confidence: 99%
“…( 2020 ) 440 mg chlortetracycline/kg feed; Amachawadi et al. ( 2011 ), 500 mg chlortetracycline/kg feed). Other three studies in weaned piglets showed that dietary chlortetracycline supplementation did not have a growth‐promoting effect in piglets at 75 mg chlortetracycline/kg feed (Long et al.…”
Section: Assessmentmentioning
confidence: 99%
“…Dietary chlortetracycline supplementation (at 30 mg/kg feed) had a growth-promoting effect in pigs for fattening. Amachawadi et al (2011) studied in pigs the effect of feeding grade antimicrobials and copper on performance. A total of 240 weaned piglets (unspecified breed/genotype; 34 days of age, BW 7.7 kg) were used in a 35-day growth trial to compare the effects of copper (Cu, from copper sulfate) and feed grade antimicrobials in a 2 9 3 factorial design (the factors being copper level 16.5 and 141.5 mg Cu/kg feed and antimicrobial level 0 or chlortetracycline or tylosin supplementation).…”
Section: Studies In Pigsmentioning
confidence: 99%
See 1 more Smart Citation